Chinese Journal of Mechanical Engineering - Song, Tianhu
Chinese Journal of Mechanical Engineering (CJME) was launched in 1988. It is a peer-reviewed journal under the govern of China Association for Science and Technology (CAST) and sponsored by Chinese Mechanical Engineering Society (CMES).   As the only official journal of CMES, CJME has been one of the top journals in Mechanical Engineering in China, aiming to become a world-class one. On behalf of CMES, CJME serves for international communication among over 80 international societies/institutions, such as American Society of Mechanical Engineers (ASME), Institution of Mechanical Engineers (IMechE), and International Federation for the Promotion of Mechanism and Machine Science (IFToMM), etc. CJME welcomes original research articles, reviews, letters, research highlights, and editorials.   The publishing scopes of CJME follow with: - Mechanism and Robotics, including but not limited to -- Innovative Mechanism Design -- Mechanical Transmission -- Robot Structure Design and Control -- Applications for Robotics (e.g., Industrial Robot, Medical Robot, Service Robot…) -- Tri-Co Robotics - Intelligent Manufacturing Technology, including but not limited to -- Innovative Industrial Design -- Intelligent Machining Process -- Artificial Intelligence -- Micro- and Nano-manufacturing -- Material Increasing Manufacturing -- Intelligent Monitoring Technology -- Machine Fault Diagnostics and Prognostics - Advanced Transportation Equipment, including but not limited to -- New Energy Vehicle Technology -- Unmanned Vehicle -- Advanced Rail Transportation -- Intelligent Transport System - Ocean Engineering Equipment, including but not limited to   --Equipment for Deep-sea Exploration   -- Autonomous Underwater Vehicle - Smart Material, including but not limited to   --Special Metal Functional Materials --Advanced Composite Materials --Material Forming Technology  .